Survei Penyakit Busuk Pangkal Batang Kelapa Sawit di Kebun Cikasungka, PT Perkebunan Nusantara VIII, Bogor - Amelia Salsabila; Evan Purnama Ramdan; Paranita Asnur; Hendi Hidayat (Agrosains : Jurnal Penelitian Agronomi, 2022)
Oil palm (Elaeis guineensis Jack) is an important plantation commodity for both agriculture and the economy, because its oil-producing potential is greater than that of other crops, such as corn, soybean and sunflower oil. The main disease of this plant is stem rot (BPB) caused by Ganoderma boninense. Therefore, it is necessary to know the incidence and severity of the disease as well as the control efforts that have been carried out at PTPN VIII Palm Oil Plantation, Cikasungka. The study used a Randomized Block Design with 3 observation blocks that had Ganoderma boninense attack each covering an area of 25 ha, each block taken 5 observation plots with an area of 50 x 50 m2 each (4 on the edge of the block and 1 in the middle of the block), then from each plot, 5 sub-plots measuring 10 x 10 m2 were taken (4 at the edges of the plot and 1 in the middle of the plot). Observational data were analyzed with variance and further tested by Duncan Multiple Range Test. The results of this study indicate that the symptoms of disease in the garden are very diverse, ranging from mild to very severe. The signs of the disease can be identified through the fruiting bodies of Ganoderma boninense. The incidence of disease in all survey locations ranged from 16 – 38%, where B3 was significantly different from B1. The lowest percentage of disease severity was in location B3 (5.75%) which was statistically significantly different from location B1. Location B1 had the highest disease severity, which was 23%. The control of BPB that has been carried out at the survey site includes the construction of isolation trenches followed by the application of biofungicides with the active ingredients of T. koningii and T. harzianum.